Faktor-Faktor Yang Mempengaruhi Implementasi Sistem Informasi Manajemen Daerah (SIMDA) Pada Opd Kota Langsa - Silva Humaira; Afrah Junita; Nasrul Kahfi Lubis (Universitas 17 Agustus 1945 Semarang, 2024)
The government implements the Regional Management Information System (SIMDA) with the aim of facilitating financial management to achieve reliable financial reports and as a reference in decision-making. The purpose of this study is to identify the impact of user understanding, top management support, and user interest on SIMDA implementation. The research adopts a quantitative approach by collecting primary data through questionnaires distributed to 72 respondents from 24 Regional Device Organizations (OPD) in Langsa City, using purposive sampling method. Data analysis is conducted through multiple linear regression using IBM SPSS 25 software. The study results indicate that user understanding has a significant impact on SIMDA implementation, while top management support and user interest do not have significant individual impacts. However, overall, user understanding, top management support, and user interest collectively have a significant impact on SIMDA implementation.